Can China’s Market-Oriented Reform Improve the Efficiency of Industrial Land Use? A Panel Data Empirical Analysis at Prefecture Level From 2007–2019 - Pu, Wenfang; Zhang, Anlu (Frontiers in Environmental Science, 2022)
China is entering rapid industrialization and urbanization since 1990’s with the urban land use payment reform. Nevertheless, higher rate of industrial land in construction land driving by local government-led industrial double growth competition fuels China the global biggest manufacturing giant and second largest economy on one hand, waste water, liquid and green house gas emission from industrial development has become more and more serious on the other hand, which has aroused a great concern nationally and globally. So low industrial land use efficiency (ILUE) is a big challenge besieging China at present. Whether the market-oriented reform of industrial land supply (MRIL) launched by the Chinese government can optimize the allocation of industrial land resources and improve the ILUE is urgent to be addressed at present. Basing on panel data of 270 prefecture-level cities in China from 2007 to 2019, we first construct marketization rate of industrial land (MIL) and examine the temporal and spatial change in MIL in each prefecture-level city. Then the impact of MIL on industrial land use efficiency (ILUE) is illuminated by super-efficient slacks-based measure (SBM) model including desirable and undesirable outputs. The results show that:(1) China's MRIL plays a positive role in the ILUE, but the impact is low. (2) The effect of MRIL on ILUE varies regionally, namely higher economic development and higher the effect, and the vice versa. We suggest both the central and local governments should target policy reform regarding the land market development and regional economic development. The research will contribute to ongoing market oriented and economic reform both in China and the transitional economies worldwide.